Metaphysical horror - Kolakowski, Leszek; Kolakowska, Agnieszka (Chicago University of Chicago Press, 2001)
For over a century philosophers have argued that philosophy is impossible or useless, or both. Although the basic agenda dates back to the days of Socrates, there is still disagreement about the nature of truth, reality, knowledge, good and God. This may make little practical difference to our lives, but it leaves us with a feeling of radical uncertainty described by Kolakowski as 'metaphysical horror'. Is there any way out of this cul-de-sac? This trenchant analysis confronts these dilemmas head on.